Matrix-free human 2D organoids recapitulate duodenal barrier and transport properties - Kopano Valerie Masete; Dorothee Günzel; Jörg-Dieter Schulzke; Hans-Jörg Epple; Nina A. Hering (BMC Biology)
Abstract Background Traditionally, transformed cell line monolayers have been the standard model for studying epithelial barrier and transport function. Recently, intestinal organoids were proposed as superior in recapitulating the intestine. Typically, 3D organoids are digested and seeded as monolayers on gelatinous matrix pre-coated surfaces for anchorage. As this coat could potentially act as a diffusion barrier, we aimed to generate robust human duodenum-derived organoid monolayers that do not need a gelatinous matrix for anchorage to improve upon existing models to study epithelial transport and barrier function. Results We characterized these monolayers phenotypically regarding polarization, tight junction formation and cellular composition, and functionally regarding uptake of nutrients, ion transport and cytokine-induced barrier dysfunction. The organoid monolayers recapitulated the duodenum phenotypically as well as functionally regarding glucose and short-chain fatty acid uptake. Tumour necrosis factor-alpha induced paracellular transport of 4-kDa Dextran and transcytosis of 44-kDa horseradish peroxidase. Notably, forskolin-stimulated chloride secretion was consistently lower when organoid monolayers were seeded on a layer of basement membrane extract (BME). Conclusions BME-free organoid monolayers represent an improved model for studying transcytotic, paracellular but especially transcellular transport. As BME is extracted from mice, our model furthers efforts to make organoid culture more animal-free.